PEMBELAJARAN BERBASIS STUDENT-CENTERED LEARNING PADA MATERI PENDIDIKAN AGAMA ISLAM - Zulvia Trinova (AT-TA'LIM, 2013)
A professional teacher -  the one who does not only master the subject, but also be competent in selecting certain model – is really needed to carry out the teaching and learning process.  One of the alternative learning models that may activate students is Student-Centered Learning (SCL).  This model provides students with the opportunity to actively participate independently in his learning, be responsible and initiate to his learning needs.